Relationships between otolith size and fish length in some mesopelagic teleosts (Myctophidae, Paralepididae, Phosichthyidae and Stomiidae). Issue 3 (4th August 2015) - Battaglia, P.; Malara, D.; Ammendolia, G.; Romeo, T.; Andaloro, F.
<x xml:space="preserve">Abstract</x> Length–mass relationships and linear regressions are given for otolith size (length and height) and standard length (LS) of certain mesopelagic fishes (Myctophidae, Paralepididae, Phosichthyidae and Stomiidae) living in the central Mediterranean Sea. The length–mass relationship showed isometric growth in six species, whereas linear regressions of LS and otolith size fit the data well for all species. These equations represent a useful tool for dietary studies on Mediterranean marine predators.